COLCONF: Collaborative ConvNet Features-based Robust Visual Place Recognition for Varying Environments - Hafez, A. H. Abdul; Tello, Ammar; Alqaraleh, Saed (SPRINGER HEIDELBERG)
Several deep learning features were recently proposed for visual place recognition (VPR) purpose. Some of them use the information laid in the image sequences, while others utilize the regions of interest (ROIs) that reside in the feature maps produced by the CNN models. It was shown in the literature that features produced from a single layer cannot meet multiple visual challenges. In this work, we present a new collaborative VPR approach, taking the advantage of ROIs feature maps gathered and combined from two different layers in order to improve the recognition performance. An extensive analysis is made on extracting ROIs and the way the performance can differ from one layer to another. Our approach was evaluated over several benchmark datasets including those with viewpoint and appearance challenges. Results have confirmed the robustness of the proposed method compared to the state-of-the-art methods. The area under curve (AUC) and the mean average precision (mAP) measures achieve an average of 91% in comparison with 86% for Max Flow and 72% for CAMAL.
Keywords: Visual place recognition; Deep learning; Regions of interest